PRESERVASI KAWASAN PERDAGANGAN KOTAGEDE YOGYAKARTA DENGAN PENDEKATAN ADAPTIVE REUSE - Yetti, Aprodita Emma (Universitas Aisyiyah Yogyakarta, 2018)
Abstract: Pasar Gede Kotagede had a role as the center of the economy since the Islamic Mataram empire stands. Pasar Gede and surroundings has an attraction for people and travelers to come and stay in Kotagede. Cultural acculturation not only show up from the social side but also appears in the architectural. However, the development of the era and the residents as slowly erode the architectural form in the buildings and the area around Pasar Gede. This research uses qualitative explorative method to study the theory with